Development of Physiotherapy Standard Operating Procedures Case of Ankle Sprain in Basketball Players - Aulia Rahmi; Totok Budi Santoso (UNIB Press, 2024)
Physiotherapy is a form of health service aimed at individuals and groups as maintaining and restoring body movement functions throughout life. Ankle Sprain is a stretching or tearing that occurs due to (overstretch) trauma to the lateral ligament complex, due to inversion and plantar flexion movements that occur excessively when the foot is unable to provide perfect support on the floor/ground. A common injury to the ankle is Ankle Sprain, a sports injury that often occurs in volleyball and basketball players. To develop Standard Operating Procedures in performing physiotherapy treatment in chronic Ankle Sprain cases. This study was conducted using the research method of developing physiotherapy operational standards with this ankle sprain injury handling model starting with preliminary studies, history taking, assessment, diagnosis, intervention, and evaluation. The type of research conducted is Quantitative research using quasi experimental methods with pretest-posttest control group design. Experimental and control groups conducted an initial test. Both groups received different treatments, where the experimental group received thrust manipulation intervention and the control group received non thrust intervention in the form of myofascial release. There was a significant reduction in pain after manipulation therapy with the thrust and nonthrust methods on two groups were measured using the Numeric Rating Scale and after being evaluated for two weeks the pain did not increase. The provision of thrust and nonthrust manipulation therapy measures is highly recommended for the treatment of ankle pain. However, between the two methods there has not been. However, there is no significant difference between the two methods given the limited time of the study.